Econometric modeling and forecasting of environmental conditions of cities and population health problems: case study of Navoi and Zarafshan cities - Latipov, Normurod; Komilova, Nilufar; Makhmudov, Bakhodirjon; Berdiev, Khayriddin; Moslemzadeh, Mehrdad; Chulliyev, Suhrob; Murtazayev, Isabek; Hamroyev, Mukhtor (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
This study explores the connection between atmospheric emissions of harmful substances and population morbidity indicators in Navoi and Zarafshan, two highly industrialized cities in Uzbekistan’s arid climate. With industrialization in arid environments presenting unique health risks, the research seeks to deepen scientific understanding of pollution-related health impacts specific to these cities. Identifying the health effects of air pollution in urbanized, dry regions not only advances scientific knowledge but also informs public health policies, contributing to the UN Sustainable Development Goal (SDG) 11.A review of recent studies shows extensive evidence linking industrial air pollution to adverse health effects, such as respiratory, cardiovascular, and immune system issues. However, few studies focus specifically on the unique challenges faced by industrial cities in arid regions like Navoi and Zarafshan, where pollutant types and environmental interactions may differ significantly. Existing research associates industrial emissions with general morbidity rates, yet it lacks detailed analyses of how pollutants specifically affect health outcomes in arid climates.Unresolved aspects of the problem include a generalized approach in correlating air pollution with health deterioration without considering how pollutants impact health differently across various climatic and environmental contexts. The effects of pollution in arid regions, with distinct pollutant composition and dispersal patterns, remain underexamined in current environmental health research.The primary goal of this research is to quantify and evaluate the relationships between industrial air pollutants and morbidity indicators, particularly focusing on respiratory, immune, neurological, and digestive health in Navoi and Zarafshan. By providing actionable data on these connections, the study intends to guide health interventions to reduce health risks associated with industrial emissions in these areas. The purpose is to offer empirical evidence that supports policymakers and public health professionals in developing effective strategies to mitigate pollution-related health challenges in industrialized arid regions.The findings of this research indicate a strong correlation in Navoi between annual pollutant emissions and increased rates of respiratory, immune, and neurological conditions, suggesting these health issues are particularly sensitive to pollution in the city. In Zarafshan, however, a different pattern is observed, with pollutants more closely associated with digestive diseases. This regional variation suggests that pollution’s health impacts may vary significantly depending on local environmental conditions.In conclusion, the study confirms a significant relationship between environmental conditions and public health, demonstrating that industrial emissions notably impact morbidity rates in arid, urban settings. By establishing these connections, the research supports SDG 11’s mission to create sustainable and healthy urban environments, presenting evidence-based recommendations to minimize the health impact of industrial pollution. The proposed measures focus on addressing the primary health challenges–respiratory, immune, neurological, and digestive issues–identified in the Navoi region, promoting healthier urban environments through targeted interventions.